Understanding the Characteristics of Dispute Settlement in Sharia Economic System - Hamid, M. Arfin (Hasanuddin Law Review, 2017)
One of the most developed areas of Islamic law (sharia) today is âFiqh Muamalah Iqtishadiyyahâ or known as term âSharia Economics.â The outcomes of the research indicate that the characteristics of sharia dispute are important to be understood by sharia businessmen and law enforcers. As it turns out in practice, however, it has certain weaknesses, particularly in view of the accountability and legitimacy aspects of its establishment. The sharia economic disputes, whether through litigation or non-litigation is not a means to profit, but solely to resolve disputes in accordance with sharia principles. the settlement of sharia disputes is still not fully independent or free from conventional law that has been going during this in the religious courts. Responding this matter throughout the process of settlement is not contradictory to the principles of sharia can be accommodated while preparing sharia-based sharia dispute law